Critical Success Factors: an Analysis of some factors at a Nuclear Power utility in South Africa - Galetta, Wilhelmina (Department of Construction Economics and Management, 2022)
Background: Over the years literature mainly focussed on time, cost and quality, also known as the triple constraint or ‘iron triangle', as the main factors to be considered as important for project success. Since then, many other factors were considered by various authors with the most cited being the work of Pinto and Slevin in 1988 who produced the Project Implementation Profile (PIP) which expanded on the triple constraint and listed ten Critical Success Factors (CSF) to be considered toward project success. The indication was that the success of projects can be improved if these factors were considered across the lifecycle of the project and they can be tailor-made to be specific to a particular industry. With this in mind, this research study has been conducted at a nuclear power plant (NPP) and it explores the applicability of the CSFs of the PIP towards nuclear project success. Purpose: The purpose of the thesis/dissertation was to gain and understanding from various stakeholders of what constitutes CSFs for projects undertaken at a NPP in South Africa; testing if those listed in the PIP would suffice or if additional factors need to be included specifically for nuclear projects. Research objectives: The research study considered the following research objectives: Understanding which CSFs of the PIP were important for nuclear projects and evaluate which of them are perceived by various stakeholders to be important to nuclear project success. Thereafter some CSFs of the PIP were analysed towards identifying if there were factors not included in the PIP but that were pertinent to nuclear project success. Research design and methodology: A mixed methods approach was adopted to this research. An interpretive case-study was conducted post event to understand phenomena through the participants' interpretation of their context. The case-study methodology was chosen and data collected using multiple data sources such as interviews with project managers who had successfully implemented projects and some system engineers who had conducted effectiveness reviews on such projects, gleaning the database of completed projects as well as Operating Experience (OE) / lessons learnt at Koeberg Nuclear Power Station (KNPS). This was done to determine the common factors that led to the analysed projects' individual success. Multiple cases at KNPS and the factors considered for nuclear project success, outside of the CSFs of the PIP were used to conduct the research. The design methodology used towards getting to the CSF framework for nuclear projects was informed by factors considered by the World Organisation of Nuclear Operators (WANO), Institute for Nuclear Plant Operators (INPO) and the International Atomic Energy Agency (IAEA), all organisations that are key role players in the nuclear field. This paper utilised tools and techniques to demonstrate how a framework for determining nuclear project success can be adopted. Research findings: The results revealed that while CSFs were generally understood but not known in the PIP format. Furthermore, in order for the CSFs to be applicable to nuclear project success, additional factors that are pertinent to nuclear projects needed to be included and a specific framework developed accordingly. Research Limitations: The research study focused on projects within the nuclear project management department (NPM), in order to simplify the data collection process. Strategic information that was deemed as sensitive or confidential could not be revealed explicitly during the course of data gathering and therefore inferences had to be made. Another limitation was the timing of the distribution which took place during an outage, yielding a low response rate during the allotted time compelling the Researcher to extend the time period for data collection. Finally, the uneven distribution of responses in the various phases of the nuclear project lifecycle posed a challenge with the Execution Phase being the dominating phase. This uneven distribution of results meant that the overall findings would be governed by the Execution Phase. This had an implication on the generalisability of the results. Furthermore, with the respondents' ratings of the CSF being subjective; this may have had an impact on the accuracy of results. Originality: The CSF framework for nuclear project success, when applied can provide valuable pointers for Koeberg and the nuclear industry when implementing nuclear projects for success. Practical implication: This information can be shared across NPM and related departments who form part of the nuclear project lifecycle. The information and lessons learned can also be shared in the nuclear industry by way of OE. The paper will benefit other NPP operators in applying the CSFs that are introduced in the framework to nuclear projects and provide them with the ability to monitor and control nuclear project success at each phase of the nuclear project lifecycle towards ensuring nuclear project success. The framework will allow the project manager and project team to identify, analyse, respond and monitor and control CSFs that project participants should plan for to ensure nuclear project success so as not to negatively impact the plant and the business at large with dire consequences that are introduced by project failure.